Mengapa Etika Penting di Era Digital? (International Forum of Researchers and Lecturers, 2024)
In the digital era, communication ethics has become increasingly crucial because the rapid development of information and communication technology has changed the way people interact and share information. Digital ethics involves the principles and norms that govern user behavior in creating, disseminating, and consuming content responsibly. Ethics and morals are related to each other. Morals are attitudes or actions while ethics are the values ​​contained therein. So, ethics is a rule of human behavior or habits that emphasizes what is good and what is bad. This research aims to find out how important communication ethics is in the digital era. The research method used is a literature study by collecting various journals and articles related to ethics and communication in the digital era. The results of this research reveal that ethics is very important in this digital era.